(untitled) (Global Journal of Medical Research, 2016)
Patients with cleft lip and palate undergo various problems and managing these patients by prosthesis has been a challenge for many years and the problems begin with making of impression. The authors describe a chair-side technique for facial moulage in cleft infants that is simple, efficient and inexpensive while still being safe for the infant.